THE IMPORTANCE OF A METHODOLOGICAL MODEL IN DEVELOPING THE PROFESSIONAL COMPETENCE OF CADETS IN MILITARY EDUCATIONAL INSTITUTIONS OF THE MINISTRY OF DEFENSE - Yuldashev Askar Khudoyberdiyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article describes the place and role of a methodological model in improving the professional competencies of cadets in higher military educational institutions.